Self-esteem and body image satisfaction in women with PCOS in the Middle East: Cross-sectional social media study - Alkheyr, Zainab; Murad, Mariam; Das, Priya; Aljenaee, Khaled; Kamel, Charlotte; Hajji, Sulaiman Ali; Flood, John; Atkin, Stephen L.; Ali, Khawla F. (PLOS ONE, 2024)
Background Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of childbearing age, associated with increased incidence of emotional disorders, anxiety and depression. Objective The aim was of this study was to investigate whether those women reporting PCOS differed to women without PCOS in measures of psychological well-being including body-image satisfaction and self-esteem across a Middle Eastern population. Materials and methods An online survey link of 21 questions was shared and distributed across social media platforms (Instagram and WhatsApp). The main outcome measured was levels of self-esteem and body image satisfaction in association with symptoms experienced by the participants. Results 12,199 female subjects completed the survey of whom 3,329 respondents (27.3%) self-reported a diagnosis of PCOS. PCOS respondents felt less attractive compared to non-PCOS respondents (73.9% vs 80.5%, p<0.0001). More respondents with PCOS reported avoidance of their reflection in the mirror (61.7% vs 49.8%, p<0.001) and avoidance of social interactions (22.3% vs 32.3%, p<0.0001). More PCOS respondents wanted to lose weight (75.2% vs 68.5%, p<0.001) with increasing weight being associated with being less attractive (p<0.001). Fewer PCOS respondents felt satisfied/confident compared non-PCOS respondents (38.6% vs 50.7%, p<0.001). Conclusion PCOS respondents reported significantly lower measures of self-esteem and body image satisfaction compared to non-PCOS respondents in this population.